(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
Traumatic brain injuries (TBI) is a significant cause of morbidity and mortality, leading to cognitive dysfunction, affecting patients and their families as a whole, and also greatly burdening the socioeconomic system [1,2]. Seizures in neurosurgical patients are common and can lead to several potential complications, such as higher metabolic demand of neurons, increased intracranial pressure, and secondary brain damage. Antiepileptic drug prophylaxis is commonly prescribed for the treatment of patients with traumatic brain injury, as certain subgroups have been shown to have a beneficial effect in preventing seizures [1]..